Tooth Reattachment and Palatal Veneer on a Multidisciplinary Approach of Crown Fractures in Upper Central Incisors - Vanessa Machado; Ricardo Alves; Luísa Lopes; João Botelho; José João Mendes (Case Reports in Dentistry)
Dental trauma is more common in young patients and its sequelae may have great impact on the esthetics, functions, and phonetics. This paper reports a case of trauma in both central incisors in a young 17-year-old patient who was treated using adhesive tooth fragment reattachment on tooth 2.1 and a palatal indirect composite veneer on tooth 1.1. Regarding the available literature and fracture extension, the treatment approach proposed for this case provided good functional and esthetic outcomes. Clinical and radiographic results after 1 year were successful. This case demonstrates the importance of establishing a multidisciplinary approach for successful dental trauma management.